RNA sensing by conventional dendritic cells is central to the development of lupus nephritis - Celhar, Teja (2015)
Glomerulonephritis is a common and debilitating feature of systemic lupus erythematosus (SLE). The precise immune mechanisms that drive the progression from benign autoimmunity to glomerulonephritis are largely unknown. Previous investigations have shown that a moderate increase of the innate Toll-like receptor 7 (TLR7) is sufficient for the development of nephritis. In these systems normalization of B-cell TLR7 expression or temporal depletion of plasmacytoid dendritic cells (pDCs) slow progression; however, the critical cell that is responsible for driving full immunopathology remains unidentified. In this investigation we have shown that conventional DC expression of TLR7 is essential for severe autoimmunity in the Sle1Tg7 model of SLE. We show that a novel expanding CD11b+ conventional DC subpopulation dominates the infiltrating renal inflammatory milieu, localizing to the glomeruli. Moreover, exposure of human myeloid DCs to IFN-α or Flu increases TLR7 expression, suggesting they may have a role in self-RNA recognition pathways in clinical disease. To our knowledge, this study is the first to highlight the importance of conventional DC-TLR7 expression for kidney pathogenesis in a murine model of SLE.